Inclusive photon production at forward rapidities in proton–proton collisions at √s = 0.9, 2.76 and 7 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Leardini, Lucia; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (The European physical journal. C, Particles and fields, 2015)
The multiplicity and pseudorapidity distributions of inclusive photons have been measured at forward rapidities (2.3<η<3.9) in proton–proton collisions at three center-of-mass energies, s√ = 0.9, 2.76 and 7 TeV using the ALICE detector. It is observed that the increase in the average photon multiplicity as a function of beam energy is compatible with both a logarithmic and a power-law dependence. The relative increase in average photon multiplicity produced in inelastic pp collisions at 2.76 and 7 TeV center-of-mass energies with respect to 0.9 TeV are 37.2 ± 0.3 % (stat) ± 8.8 % (sys) and 61.2 ± 0.3 % (stat) ± 7.6 % (sys), respectively. The photon multiplicity distributions for all center-of-mass energies are well described by negative binomial distributions. The multiplicity distributions are also presented in terms of KNO variables. The results are compared to model predictions, which are found in general to underestimate the data at large photon multiplicities, in particular at the highest center-of-mass energy. Limiting fragmentation behavior of photons has been explored with the data, but is not observed in the measured pseudorapidity range.
*ALICE Collaboration: B. Abelev, V. Angelov, O. Busch, P. Glaessel, J. Klein, L. Leardini, D. Lohner, X.G. Lu, A. Maire, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 944 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 09.07.2021